The Hepatoprotective Effect of Glycyrrhiza glabra Roots Extract Against Amiodarone Induced Hepatotoxicity in Male Rats - Alzahraa Fatima Safa'a Fadhil; Yasir Mustafa Kamal; Huda Jaber Waheed (College of Pharmacy University of Baghdad, 2024)
Amiodarone (AMD), a powerful antidysrhythmic medication, can cause hepatotoxicity when used long-term or in high doses. It affects both mitochondrial and lysosomal function because of its lipophilic nature and accumulation in tissues. It also has direct production of ROS. Glycyrrhiza glabra is one of the medicinal plants that have been commonly used for thousands of years. It possesses anti-ulcer, anti-inflammatory and antioxidant properties. In this study, the antihepatotoxic effect of Gg was evaluated against AMD liver toxicity in rats model, thirty rats were taken and divided evenly into five groups given daily doses by gastric gavage oral tube for 3 weeks as follows: the 1st group acted as a control group given D.W., and the 2nd group received AMD at a dose of 300mg/kg for 2 weeks. 3rd, 4th, and 5th groups were pretreated with Gg in doses of 200, 400, and 800 mg, respectively, for one week, then along with AMD for 2 weeks. Hepatic damage, revealed by histology and the increased activities of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and serum phospholipase A2 (PLA2) was decreased in the AMD group. Gg extract significantly reduced the elevated AST and ALT levels caused by AMD intoxication, rendering PLA2 to its normal level. It also enhanced liver superoxide dismutase (SOD), glutathione (GSH), and malondialdehyde (MDA) levels. Gg extract markedly reverses the increased serum TNF levels induced by AMD; therefore, it may be considered a good hepatoprotective agent.